THE ROLE OF AN OLIGOPHRENOPEDAGOGUE IN THE INCLUSIVE EDUCATION SYSTEM - Alijonova , Dilorom (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article provides a comprehensive overview of the professional activity of the oligophrenopedagogue within the inclusive education system, including their functions, methods, and role in the successful integration of children with intellectual disabilities into the educational process. It also analyzes modern pedagogical approaches and existing challenges.